Effect of Compost Addition on Carbon Mineralization and Kinetic Characteristics in Three Typical Agricultural Soils - Shanglong Zhang; Xianni Chen; Aoxue Shi; Minggang Xu; Fenggang Zhang; Lu Zhang; Jiaojiao Zang; Xiaofeng Xu; Jiakai Gao (Agronomy)
Soil carbon is a crucial component of the global carbon cycle, and carbon mineralization is influenced by various factors. However, there is a lack of systematic analyses on the responses of carbon mineralization in different soil types to the addition of exogenous organic matter. This study investigates the effects of compost addition on the mineralization and kinetic characteristics of soil carbon across three typical agricultural soils: paddy soil, black soil, and cinnamon soil. A 210-day incubation study was conducted with four treatments: Control (un-amended soil), R (soil + straw), R1M (soil + straw + low compost application rate), R2M (soil + straw + high compost application rate). The results showed that the CO2 emission rates of the three soils were higher during the early stage (1–37 days) and decreased afterward. The CO2 emission rates of the paddy soil and the black soil were significantly higher than those of the cinnamon soil. The addition of compost significantly increased both the CO2 emission rate and the cumulative release of CO2, especially in the R2M treatment. At the end of the incubation, the SOC contents were higher in the R2M treatment than in the Control for all three soils (p < 0.05), with the most notable increase in the cinnamon soil (60.93%). Compost addition significantly enhanced the active carbon pool (Ca), slow carbon pool (Cs), and potentially mineralizable carbon pool (Cp), while decreasing the mineralization rate (ka) of the Ca, but the effect on the mineralization rate (ks) of the Cs and mineralization entropy (Cm) varied by soil types. The ks of the paddy soil was significantly reduced by 23.08% under the R1M and R2M treatments compared with the Control and R treatment. The ks of the black soil was significantly increased by 59.52% under the R2M treatment compared with the Control. The ks of the cinnamon soil was elevated considerably by 79.31% under the R2M treatment compared with the Control, R, and R1M treatments (averaging 0.29 × 10−2 d), and the ks of the paddy soil and black soil were significantly higher than those of the cinnamon soil under the R2M treatment. The Cm was significantly higher in the organic material added treatments than in the Control for the black soil and the paddy soil, but showed a higher value in the R treatment than in the R2M and Control for the cinnamon soil. In conclusion, compost addition stimulated soil carbon mineralization and improved the SOC content, especially in the cinnamon soil, while reducing the mineralization rate of the active carbon pool across the three soils. The mineralization rate of the slow carbon pool and the changes in mineralization entropy were dependent on soil types, primarily related to the initial soil nutrient contents, pH, and particle compositions. These findings offer valuable insights for managing the soil carbon pool in agricultural ecosystems.